Anatomical relationships between Wrisberg meniscofemoral and posterior cruciate ligament's femoral insertions - Heetor Campora de Sousa Oliveira; Julio Cesar Gali; Edie Benedito Caetano (Revista Brasileira de Ortopedia, 2013)
OBJECTIVE: To evaluate the frequency and morphometry of the Wrisberg's ligament and its relationships with the posterior cruciate ligament's femoral insertion. STUDY DESIGN: Controlled laboratory study. METHODS: 24 unpaired knee pieces, 12 right and 12 left were submitted to a deep dissection of the Wrisberg and posterior cruciate ligaments. The pieces were photographed with a digital camera and ruler; the Image J software was used to measure the ligaments' insertion areas, in square millimeters. RESULTS: The Wrisberg ligament was present in 91.6% of the studied pieces. In those its shape was elliptical in 12 pieces (54.54%). In 68% of the knees, the WL insertion was proximal to the medial intercondilar ridge, close to the PCL posteromedial bundle. The average area for the WL was 20.46 ± 6.12 mm2. This number corresponded to 23.3% of the PCL's average area. CONCLUSIONS: WL ligament is a common structure in knees. There is a wide variation of its insertion area. Proportionally to the PCL's insertion area the WL ones suggests that it may contribute to the posterior stability of the knee joint.